Influence of enclosure design on the behaviour and welfare of Pogona vitticeps - Melanie Denommé; Natalie L. Bakker; Glenn J. Tattersall (PLoS ONE, 2025)
Complex or naturalistic enclosures have become increasingly accepted as those best-suited to improve an animal’s welfare. However, designing such enclosures can be difficult if little is known about the animal in the wild, and enclosures that aim to replicate natural habitats must still be assessed to ensure their assumed benefits are realized. Therefore, this study examined the behaviour and physiology of captive-bred bearded dragons ( Pogona vitticeps ) living in naturalistic- and standard-style enclosures. First, we assessed whether naturalistic-style enclosures better accommodated a lizard’s behaviour by examining if lizards in these enclosures were inactive for a similar amount of time as their wild counterparts, if they used their enclosures more evenly than standard-housed lizards, and if naturalistic enclosures provided better thermal heterogeneity than standard enclosures. Then, we examined if living in naturalistic-style enclosures improved the lizard’s welfare by examining behaviours related to stress and relaxation as well as heterophil to lymphocyte (H:L) ratios. Although naturalistic enclosures did offer better thermal heterogeneity, evidence that they better accommodated a lizard’s behaviour or improved their welfare was equivocal: lizards spent the majority of their day inactive, in one area of the enclosure, and performed similar amounts of behaviours related to stress and relaxation, regardless of enclosure style. Furthermore, H:L ratios were only lower for female lizards in naturalistic enclosures. Our results may have been influenced by the timeline of data collection but could also suggest that standard enclosures are sufficient for P. vitticeps , that P. vitticeps perceive standard- and naturalistic-style enclosures as similar, or that the potential benefits of naturalistic enclosures were hampered by the enclosure’s size. Ultimately, it was apparent that structural complexity alone was insufficient to influence lizard welfare, highlighting the importance of considering the animal’s motivations throughout their life and aspects other than enrichment for effective enclosure design.